2018
DOI: 10.1364/oe.26.024854
|View full text |Cite
|
Sign up to set email alerts
|

Real time g(2) monitoring with 100 kHz sampling rate

Abstract: We introduce a technique to determine photon correlations of optical light fields in real time. The method is based on ultrafast phase-randomized homodyne detection and allows us to follow the temporal evolution of the second-order correlation function g (2) (0) of a light field. We demonstrate the capabilities of our approach by applying it to a laser diode operated in the threshold region. In particular, we are able to monitor the emission dynamics of the diode switching back and forth between lasing and spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…At 100 kHz, this number of measured quadratures amounts to approximately 750. In accordance with our earlier studies 20 , for smaller numbers of measured quadratures and, equivalently, for higher averaging frequencies f av , it is not guaranteed that all relative phases are sampled equally. Thus, the results obtained via homodyning are reliable only for f av up to 100 kHz in our setup.…”
Section: Frequency-dependent Photon Correlationssupporting
confidence: 75%
See 3 more Smart Citations
“…At 100 kHz, this number of measured quadratures amounts to approximately 750. In accordance with our earlier studies 20 , for smaller numbers of measured quadratures and, equivalently, for higher averaging frequencies f av , it is not guaranteed that all relative phases are sampled equally. Thus, the results obtained via homodyning are reliable only for f av up to 100 kHz in our setup.…”
Section: Frequency-dependent Photon Correlationssupporting
confidence: 75%
“…For the signal light fields investigated within this manuscript, the coherence times are much shorter than that, so one may safely assume that each quadrature measurement randomly samples a different relative phase between the signal and the local oscillator. Under such conditions, it has already been shown that approximately 750 quadrature measurements are sufficient to achieve a sufficient amount of phase averaging 20 . As a result, the analysis yields the mean photon number and the value of of the signal light field within the approximately time window needed to perform 750 quadrature measurements.…”
Section: Real-time Homodyne Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach to improve the CAR is to use pulsed pumping schemes that use nanosecond, [ 21 ] picosecond, [ 14,22 ] or even femtosecond [ 23 ] pulses. In previous coherence measurements with pulsed excitation, [ 24 ] the photon counts were averaged over the full pump pulse and photon statistics were compared between adjacent pulses. Additionally, very few studies have been carried out to determine the coherence trends within the emitted pulse.…”
Section: Introductionmentioning
confidence: 99%